ANALISIS PERBANDINGAN SIKAP KONSUMEN ATAS ATRIBUT PRODUK OBAT NYAMUK MEREK BAYGON DAN HIT DI KOTA PEKANBARU - Joni Fahmi; Jushermi -; Gatot Wijaya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine consumer attitudes on product attributes: brand, packaging, product quality, labeling, and product features of anti mosquito Baygon and HIT and to determine whether there are differences consumer attitude on product attribute of anti mosquito Baygon and HIT in Pekanbaru. The population in the study are the users of anti mosquito Baygon and HIT in Pekanbaru. The number of samples are 100 respondents by using Slovin formula and Quota sampling technique. The data analyzed by using multi attitude attribute model Fishbein and the Mann-Whitney U-test. From the results of the testing that has been done on the respondents have a positive attitude on product attribute: brand, packaging, product quality, labeling, and product features of anti mosquito Baygon and HIT, and Mann-Whitney U-testshowed that there are differences in consumer attitude on product attribute of anti mosquito Baygon and HIT in Pekanbaru.Keywords: Product Features, Brand, Packaging, Quality Products, Labels, and Consumer Attitudes